Penerapan media pembelajaran wordwall untuk meningkatkan keterampilan menulis kalimat berpola SPOK pada mata pelajaran Bahasa Indonesia kelas III sekolah dasar - Balqis, Rafida Aqila Sekar; Istiyati, Siti (Didaktika Dwija Indria, 2026)
This study uses wordwall media to improve the writing skills of SPOK patterned sentences in Indonesian language subjects of grade IIIB SDN Danukusuman. This study is a Classroom Action Research (CAR) which was carried out in two cycles. The subjects of this study were 26 students and teachers of grade IIIB SDN Danukusuman. Data collection techniques were tests, observation and documentation. Data validity testing techniques were source triangulation and technical triangulation. Data analysis techniques used the Miles and Huberman analysis model. The results showed that students' writing skills of SPOK patterned sentences increased in each cycle. Classical completeness in the pre-action was 26,92%, in cycle I increased to 60%, and in cycle II increased to 83,33%. The conclusion of this study is that the application of wordwall learning media can significantly improve the writing skills of SPOK patterned sentences in Indonesian language subjects of grade IIIB SDN Danukusuman.